Corrective feedback in French as a foreign language writings - Rougier, Nicolas (Glottodidactica, 2014)
The purpose of this paper is to identify the objectives pursued by teachers when correcting learners writings and show that the type of feedback used to this end is essentially the direct feedback, while other forms of feedback, presented here, are neglected. On the other hand, it seems that neither in practice nor in research corrective feedback specifically adapted to the correction of non-formal errors has been developed so far.